ANALISIS PENURUNAN DAN KESTABILAN PADA TIMBUNAN BERTAHAP DI ATAS TANAH LUNAK ( STUDI KASUS : REKLAMASI DERMAGA PETI KEMAS TANJUNG MAS SEMARANG) - Setiawan, M.Darma
Many geotechnical engineering project involve the numerous aspect of complex geotechnical problem. It considers the advanced theories in geotechnical aspect, simulating the construction process, modeling of geotechnical structures, and interaction between the structures and soil. This research takes the Tanjung Mas New Reclamation Harbor Project in Semarang as the case study. In order to complete modeling and analysis, some features of PLAXIS, finite element package program, is used to deal with the numerous geotechnical aspect. The program indicates that consist of mud layer in the top of sea bed cause unstable condition. Allowing to simulating anchorage length of sheet pile and evaluating the result can optimize the length of sheet pile. The feature of program to modeling the construction stage and considering each duration time allows for a realistic assessment of stresses and displacement as caused. The program shows clearly the different of un-drained distortion from un-drained behavior with compression behavior from drained case. The analysis resulting that in order to obtain the 9.6 m final elevation, it is required 12.0 m height fill where the expected total settlement is 2.4 m. As note, the total settlement figure from Soft Soil model is bigger than Mohr Coulomb. In addition to the analysis result, it is required to dredge the mud layer and replacing with general sand fill.